Information technologies usage for human-style designing in TV space - Залкінд, Вікторія Вікторівна; Літинська, Юлія Вікторівна (Eastern-European Journal of Enterprise Technologies, 2012)
General features of information technologies applied for human-style designing are given. The results of their usage in Kharkov regional state TV-company are shown